Current and future trends in bridge design, construction and maintenance. 2, - Das, Parag C.; Frangopol, Dan M.; Nowak, Andrzej S. (Thomas Telford, 2001)
This volume of papers from the second of these conferences, held in Hong Kong, encompasses the state-of-the-art in bridge design, construction, maintenance and safety assessment. It includes papers on major bridge schemes, both completed and under construction, and on innovative approaches used in various parts of the world.